Focused ion beam preparation of halide perovskite microscopy specimens: evaluation of the beam induced damage. (12th October 2022) - Lu, Yuan; Wang, Hao; Chen, Yi; Akriti,; Hu, Xiangchen; Dou, Letian; Mi, Qixi; Ning, Zhijun; Yu, Yi
Abstract: Focused ion beam (FIB) is currently one of the most commonly used methods for preparing transmission electron microscopy bulk specimens. However, for ion beam-sensitive materials such as halide perovskites, the ion beam milling process can easily cause decomposition and structure damage to the specimen. Here we investigate the influence factors of ion beam damage theoretically and experimentally, and successfully obtain the high-resolution transmission electron microscopy image of inorganic halide perovskite sample prepared by FIB. Theoretical investigations indicate that the temperature rises extremely fast for ion beam milling, reaching more than 80% of the highest temperature in less than one picosecond. Experimental investigations of halide perovskites in various forms (nanostructures, thin film devices, and single crystals) suggest choosing appropriate FIB acceleration voltage and beam current together with strategies to reduce the milling time may alleviate structure damage.